(untitled) (Research, Society and Development, 2022)
Objective: To analyze nursing’s contributions to child malnutrition associated with breastfeeding. Method: It encompasses an integrative literature review, a method that aims to analyze existing research and allows for an in-depth conclusion on a given topic. Results: eighteen articles were selected according to the theme, eighteen being national, fourteen different journals and published in the years 2017 to 2021. Conclusion: Malnutrition, absence or deficiency of vitamins or minerals, causes irreversible damage when they occur in the first year of life, in which early weaning is one of the factors for the cause of this problem. Nursing care, as well as the person responsible for the child, has a great role for healthy growth and development.